Maternal Mortality in Indonesia, When will it end? - Sutrisno, MD, PhD, OG (REI) (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Sad news colored the arrival of this morning. Although the sky is clear, the breeze is gentle, and the sun is shining brightly, our feelings are truly troubled. This morning, the Obstetrics and Gynecology resident, with a sad face, reported a young mother passed away in the Maternal ICU, leaving behind deep sorrow. A young mother, 28 years old, post cesarean section at another district hospital, 35 kilometer away from our city, was sent due to decreased consciousness, blood pressure 180/120, shortness of breath, oedema, and diffuse lung rales. X-ray showed severe pulmonary oedema and the oximeter indicated an O2 level of only 85 percent despite using high doses of oxygen. 10 days of treatment in the ICU with a ventilator did not help, and this morning she was called back to God Almighty.